Indigenizing education : transformative research, theories, and praxis - Garcia, Jeremy; Shirley, Valerie; Kulago, Hollie Anderson (Research for social justice., 2022)
"The co-editors of Indigenizing Education: Transformative Research, Theories, and Praxis bring various scholars, educators, youth, and community voices together in ways that reimagine and recenter a learning process that embodies Indigenous education rooted in critical Indigenous studies and pedagogies. By reimagining Indigenous education, we suggest that it be rooted in opportunities for a deep analysis of the systemic processes and forces of settler colonialism which maintain structures that defy and dismiss our right to engage an education that is critical, culturally sustaining, and centers Native nation-building. Thus, reimagining and recentering an education rooted in critical Indigenous studies and pedagogies becomes a process of activating a critical Indigenous consciousness that renews and sustains goals to activate agency, social change, and advocacy for Indigenous peoples. The chapters are organized across three sections, entitled Indigenizing Curriculum and Pedagogy, Revitalizing and Sustaining Indigenous Languages, and Engaging Families and Communities in Indigenous Education. We close the book with a chapter centered on a call to action for Indigenous teaching and teacher education. We are indebted to the Indigenous youth, families, and communities who have shared their experiences with education across the chapters and who provide pathways to reconceptualize the intersection between research, theories, and praxis in Indigenous education. The co-edited book centers Indigenous epistemologies that serve as points of healing and resistance-leaving us to reaffirm, draw on, and enact Indigenous knowledge as a humanizing pedagogy and as a pedagogy of resistance. Indigenous peoples have systems of education that reflect specific knowledge, worldviews, and relations to natural elements and land which reaffirm one's Indigeneity. The contributing scholar-educators speak to the resilience and strength embedded in Indigenous knowledges. As a result, this book is a quest to understand and learn from the ways in which various Indigenous scholarship and theoretical orientations are evident and enacted with Indigenous youth and educators as well as in Indigenous learning contexts. Indigenous research and theories offers opportunities for Indigenous youth, educators, and community members to engage in transformative praxis. We perceive transformative praxis, we perceive this to be critical to any movement toward Tribal self-determination and sovereignty as it is a dialectical process that includes self-reflection and analysis of the oppressive systems. It is an intentional effort that challenges oppressive systems and applies actions to address and transform issues that have long impacted Indigenous peoples. Of significance, each of the contributors have initiated transformative praxis by activating a critical Indigenous consciousness with diverse Indigenous youth, educators, families, and community members. Across the chapters, you will observe dialogues between Indigenous and non-Indigenous scholars as they enacted various theories, shared stories, applied various curriculum and teaching practices, and reflected on the process of engaging in critical dialogues that generates a (re)new(ed) spirit of hope and commitment to intellectual and spiritual sovereignty. The book makes significant contributions to the fields of critical Indigenous studies, critical and culturally sustaining pedagogy, and decolonization. Each of these field are beneficial for Indigenous education, sovereignty, and Native nation-building"--